2020
DOI: 10.1101/2020.07.23.20160796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“PLEXIT - Therapeutic plasma exchange (TPE) for Covid-19 cytokine release storm (CRS), a retrospective propensity matched control study”

Abstract: Importance: Cytokine release storm (CRS) plays pivotal role in pathophysiology and progression of COVID-19. Objective: To evaluate the outcomes of COVID-19 patients having CRS treated with Therapeutic Plasma Exchange (TPE) as compared to controls not receiving TPE. Design: Retrospective propensity score (PS) matched analysis, 1st April to 30th June 2020. Setting: Tertiary care hospital, single centre based. Participants: Using PS 1:1 matching, 90 patients were assigned 2 groups (45 receiving TPE and 45 contro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…They came up with the conclusion that the use of therapeutic plasma exchange was associated with superior overall survival, early cytokine release syndrome resolution, and time to discharge as compared to standard therapy for COVID-19. 16 Our results supported their findings. There was a strong statistically significant relationship with lesser mortality and use of TPE among patients of COVID-19 admitted in the Critical Care Unit.…”
Section: Discussionsupporting
confidence: 90%
“…They came up with the conclusion that the use of therapeutic plasma exchange was associated with superior overall survival, early cytokine release syndrome resolution, and time to discharge as compared to standard therapy for COVID-19. 16 Our results supported their findings. There was a strong statistically significant relationship with lesser mortality and use of TPE among patients of COVID-19 admitted in the Critical Care Unit.…”
Section: Discussionsupporting
confidence: 90%
“…Further, 3 retrospective, observational cohort studies including a total of 74 patients treated with plasmapheresis have reported dramatic differences in both extubation and survival. 104,196,197 The largest, a study from Pakistan of 45 COVID-19 patients treated with plasmapheresis compared to 45 propensity matched controls, reported that the mortality in the plasmapheresis treated group was 8.9% vs 38.5% in controls, HR 0.21, 95% CI 0.09-0.53, log rank .002. 197 Khamis et al in Oman published on 31 COVID-19 patients in moderate to severe respiratory failure where 11 of the more severely ill patients received TPE with a slightly higher proportion of the TPE group also receiving tocilizumab compared to controls.…”
Section: Salvage Therapymentioning
confidence: 99%
“…These findings suggest that TPE, especially along with convalescent plasma infusion at the end of the procedure, can be an effective treatment for COVID-19 [53]. A randomized controlled clinical trial recently demonstrated that TPE is an effective treatment for COVID-19 [55]. Other specific targets of TPE include highly charged proteins identified as having a high probability of losing stability due to oxidation with age.…”
Section: Calibration Of Cytokines and Immune Responsementioning
confidence: 99%